Exploration of Knowledge and Compliance Behavior of The Coastal Community in Application of Covid-19 Health Protocol - Toha, Mukhammad; Zuhroidah, Ida; Sujarwadi, Mokh. (Universitas Aisyah Pringsewu, 2021)
Covid-19 is a deadly pandemic and spreads quickly to the community, especially those who have unhealthy lifestyles, including Panggungrejo coastal residents who have low educational characteristics, like to gather, less clean environment, and less positive attitude towards healthy living which can have an impact on the level of compliance of citizens. in implementing the Covid-19 prevention protocol. This study aims to explore the behavior of the coastal community of Panggungrejo in implementing 5 M as an effort to prevent the spread of the Covid-19 disease. This study uses qualitative methods by conducting interviews and observations to understand the existing phenomena thoroughly and in detail starting from data processing, data triangulation, and data analysis. The subjects in this study were the coastal communities of Panggungrejo. The sampling technique used purposive sampling until saturation or similarities of answers were found from the research subjects. The behavior of the coastal communities of Panggungrejo who do not comply with the implementation of 5 M is motivated by interrelated factors including low knowledge, wrong judgments about the importance of prevention before illness, a tendency to have a temperament of indifference, and lack of attention to environmental health, as well as a low economy causing a lack of availability of health facilities. In addition, the community also respects and obeys religious leaders, namely Kyai. The results of this study imply that the behavior of coastal communities who are less compliant with health protocols as a response to weak determinants, it is also revealed that these coastal communities are very respectful and obedient to religious leaders, namely Kyai. The contribution of this research is as basic data for further researchers to develop creative methods to change the health behavior of coastal communities by actively involving religious leaders. Covid-19 merupakan pandemi mematikan danmenyebarsecara cepat pada masyarakat terutama yang memiliki perilaku hidup kurang sehat, termasuk warga pesisir Panggungrejo yang mempunyai karakteristik pendidikan yang rendah, suka berkumpul, lingkungan kurang bersih dan sikap hidup sehat kurang positif yang dapat berdampak pada tingkat kepatuhan warga dalam melaksanakan protocol pencegahan Covid-19. Penelitian ini bertujuan untuk mengeksplorasi perilaku masyarakat pesisir Panggungrejo dalam menerapkan 5 M sebagai upaya pencegahan penyebaran penyakit Covid-19. Metode pada Penelitianini yaitu kualitatif dengan collecting data secara observasi dan wawancara untuk memahami fenomena yang ada secara menyeluruh dan rinci mulai dari pengolahan data, triangulasi data, dan analisis data. Subyekdalam penelitian ini adalah masyarakat pesisir Panggungrejo. Teknik pengambilan sampel menggunakanpurposive sampling sampai ditemukan kejenuhan atau kesamaan jawaban dari subjek penelitian. Perilaku masyarakat pesisir Panggungrejo yang kurang mematuhi penerapan 5 M dilatarbelakangi oleh factor yang saling terkait antara rendahnya pengetahuan, penilaian yang salah tentang pentinya pencegahan sebelum sakit, cenderung temperamen sikap tak acuh dan kurang perhatian terhadap kesehatan lingkungan, juga ekonomi yang rendah menyebabkan kurangnya ketersediaan sarana kesehatan, masyarakat juga sangat menghormati dan mematuhi tokoh agama yaitu Kyai. Hasil penelitian ini menyiratkan bahwa perilaku masyarakat pesisir yang kurang patuh terhadap protocol kesehatan sebagai respon terhadap factor determinan yang lemah, terungkap pula bahwa masyarakat pesisir ini sangat menghormati dan patuh pada para tokoh agama yaitu Kyai. Penelitian ini dapat berkontribusi pada peneliti selanjutnya sebagai data awal atau dasar untuk mengembangkan metode kreatif merubah perilaku kesehatan masyarakat pasisir dengan melibatkan tokoh agama secara aktif.